SUBSIDENCE AND HEAT PROPAGATION MODELING ON THE UNDERGROUND COAL GASIFICATION (CASE STUDY AT MUARA ENIM FORMATION, SOUTH SUMATERA) - Zulfahmi Zulfahmi; Ildrem Syafri; Abdurrokhim Abdurrokhim; Ridho Kresna Wattimena (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2020)
One of the important issues to study underground coal gasification (UCG) is the prediction of surface subsidence. Several parameters that influence these conditions are the thickness of cap rock, the physical and mechanical characteristics, the structure condition, the minerals composition of the rock, and external conditions. This study had been carried out simulation and modeling to determine the level of surface subsidence risk and the effect of high temperatures due to the activities. The modeling results show that the thickness of the rock above the UCG coal seam greatly affects the surface subsidence. The depth is more than 200 m and found that the SF value is 1.59 which indicates UCG reactor depth of ≥ 200 m is safe from the risk of subsidence. From the characteristic aspect of the cap rock, the claystone types which not contain kaolinite minerals are more prone to collapse than those of contain kaolinite minerals. From this models, the gasifier at 150 m depth was estimated that there will be a decline of -7.23 m, and the minimum subsidence is at 275 m about 0.1 m. The heat propagation modeling results show that at 50 m the temperature is estimated to be 213- 289°C, but if the thickness of the cap rock is > 200 m depth, the temperature is around 29-28°C.